KALIMAT PASIF DALAM BAHASA INGGRISDAN BAHASA INDONESIA: SUATU ANALISIS KONTRASTIF - Mustika, Nova (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Contrastive analysis is a method that can be used to help the difficulties of a teacher in teaching a second language to their students, where learning a second language is strongly influenced by the mastery of the mother tongue. The purpose of this article is to describe comparison of passive sentences in Indonesian and English. The method of this research is descriptive qualitative to provide an overview of the form of the passive sentence and find differences and similarities between passive sentencesin Indonesian and English. Examples was created by the author herself taking into account the level of general acceptance by referring to the book of Tata Bahasa Indonesian and English Grammar. Passive sentences in Indonesian are characterized by use of the